If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 = (4z + 3z) + -11 Combine like terms: 4z + 3z = 7z 17 = (7z) + -11 17 = (7z) + -11 Reorder the terms: 17 = -11 + (7z) Solving 17 = -11 + (7z) Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '(-7z)' to each side of the equation. 17 + (-7z) = -11 + (7z) + (-7z) Combine like terms: (7z) + (-7z) = 0 17 + (-7z) = -11 + 0 17 + (-7z) = -11 Add '-17' to each side of the equation. 17 + -17 + (-7z) = -11 + -17 Combine like terms: 17 + -17 = 0 0 + (-7z) = -11 + -17 (-7z) = -11 + -17 Combine like terms: -11 + -17 = -28 (-7z) = -28 Divide each side by '-7'. z = 4 Simplifying z = 4
| x+2y+2z=29 | | 17=11-(4z+4z) | | (x-3+3i)(x+3-3i)=0 | | (x+3+3i)(x+3+3i)=0 | | -0.25+3x=8.75 | | -5x(2x-9)=2(x-8)-11 | | f(x)=8ln(16x-10)+7 | | 4x^7-28x^6=-48x^3 | | sqrt(x+5)-sqrt(x-3)=2 | | y+8.4=-10.1 | | -(x+12)=24 | | (2x+1)(3x+4)=4 | | (x-3+3i)(x+3+3i)=0 | | 41=(8r-6r)+11 | | 1+a=20 | | 3x+7x-10=90 | | 41=11+(8r+6r) | | (x-4)-(2x-1)=0 | | 2x^3+8x^2+12x+6=0 | | 3x^2-2x-5=y | | 4(d-6)=28 | | V^2+9= | | 6a-10-2a=a+20 | | x+3(x+8)=132 | | (-1-x)(8-x)=0 | | 2n+(2n+4)=100 | | 15x^3-12x= | | (4-x)(x-2)=0 | | 3x^2-24x+144=y-27+144 | | 6x+8=2x+6 | | -4x+2=21x-20 | | 4y-2(y+8)=5+3(y-6) |